Ignazio Cazzaniga, in memoriam (ACME, 2024)
Ignazio Cazzaniga (1911-1974) was for many years Professor of Latin at Milan State University. During the Second World War, after the armistice of Sept. 8th 1943, he was taken prisoner by the Germans in Rhodes, and transferred to the German prison camp of Sandbostel, together with thousands of Italian officers and soldiers. This paper publishes with translation and commentary a Latin poem that was composed there by him, as a small example of the rich cultural and intellectual life which was preserved with strong determination by Italian prisoners, in spite of hunger, diseases and indignities they all suffered in that awful situation.
Keywords: Ignazio Cazzaniga; An unpublished Latin poem; Inprisonment in German concentration camps; Second World War; Struggle for intellectual dignity